Stem cells and bio scaffolds for the treatment of cardiovascular diseases: new insights - Razavi, Zahra Sadat; Farokhi, Simin; Mahmoudvand, Golnaz; Karimi-Rouzbahani, Arian; Farasati-Far, Bahareh; Tahmasebi-Ghorabi, Samaneh; Pazoki-Toroudi, Hamidreza; Saadat-Fakhr, Masoud; Afkhami, Hamed (Frontiers in Cell and Developmental Biology, 2024)
Mortality and morbidity from cardiovascular diseases are common worldwide. In order to improve survival and quality of life for this patient population, extensive efforts are being made to establish effective therapeutic modalities. New treatment options are needed, it seems. In addition to treating cardiovascular diseases, cell therapy is one of the most promising medical platforms. One of the most effective therapeutic approaches in this area is stem cell therapy. In stem cell biology, multipotent stem cells and pluripotent stem cells are divided into two types. There is evidence that stem cell therapy could be used as a therapeutic approach for cardiovascular diseases based on multiple lines of evidence. The effectiveness of stem cell therapies in humans has been studied in several clinical trials. In spite of the challenges associated with stem cell therapy, it appears that resolving them may lead to stem cells being used in cardiovascular disease patients. This may be an effective therapeutic approach. By mounting these stem cells on biological scaffolds, their effect can be enhanced.